2008
DOI: 10.1128/aem.00226-08
|View full text |Cite
|
Sign up to set email alerts
|

Two Angular Dioxygenases Contribute to the Metabolic Versatility of Dibenzofuran-Degrading Rhodococcus sp. Strain HA01

Abstract: Rhodococcus sp. strain HA01, isolated through its ability to utilize dibenzofuran (DBF) as the sole carbon and energy source, was also capable, albeit with low activity, of transforming dibenzo-p-dioxin (DD). This strain could also transform 3-chlorodibenzofuran (3CDBF), mainly by angular oxygenation at the ether bond-carrying carbon (the angular position) and an adjacent carbon atom, to 4-chlorosalicylate as the end product. Similarly, 2-chlorodibenzofuran (2CDBF) was transformed to 5-chlorosalicylate. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 60 publications
0
33
0
1
Order By: Relevance
“…DF412 (BAG06223)1 dxnA1 Miyauchi et al, 2008d2 Rhodococcus sp. HA01 (ACC85677)1Aly et al, 2008d2 Terrabacter sp. YK1 (BAG80728)1Iida et al, 2002ad2 Rhodococcus sp.…”
Section: Table A1mentioning
confidence: 99%
“…DF412 (BAG06223)1 dxnA1 Miyauchi et al, 2008d2 Rhodococcus sp. HA01 (ACC85677)1Aly et al, 2008d2 Terrabacter sp. YK1 (BAG80728)1Iida et al, 2002ad2 Rhodococcus sp.…”
Section: Table A1mentioning
confidence: 99%
“…strain DF412 (33) and Rhodococcus sp. strain HA01 (3). These results suggest that DF-utilizing actinomycetes recently acquired dfd gene clusters by lateral gene transfer.…”
mentioning
confidence: 51%
“…The dfd catabolic pathway genes have been identified in at least four genera of actinomycetes (3,20,21,33,44), and the levels of nucleotide sequence conservation are high. By using Southern hybridization analysis, we determined that the transcription regulator gene dfdR was highly conserved in all six strains of DF-utilizing actinomycetes that we isolated and analyzed (data not shown), suggesting that dfdR was laterally transferred as a part of the dfd gene cluster in several DFutilizing actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…HA01 expressed no enzyme activity in E. coli. 14,19,21) The biphenyl dioxygenase genes bpdC1C2BA of Rhodococcus sp. strain M5 expressed slight activity in E. coli, 42) but no reports have described the details of the reason they were scarcely expressed.…”
Section: Discussionmentioning
confidence: 99%
“…13 ing difficulty in expressing enzyme activity of actinomycete enzyme genes other than BphA in E. coli. [16][17][18][19][20][21] In this study, expression of RHA1 BphA genes, bphAaAbAcAd was examined in detail to achieve functional expression of it in E. coli. We found that the lack of bphAaAbAcAd-coding enzyme activity in E. coli originates from an inability of RHA1 bphAc to express its catalytic activity in E. coli.…”
mentioning
confidence: 99%